Little women - Alcott, Louisa May, 1832-1888.; Armstrong, Gillian, 1950-; Swicord, Robin; Di Novi, Denise; Ryder, Winona, 1971-; Sarandon, Susan, 1946-; Alvarado, Trina; Danes, Claire, 1979-; Columbia Pictures; Columbia TriStar Home Video (Firm) ([United States] : Columbia TriStar Home Video, 1995)
Meg, Jo, Beth, and Amy March live with their mother in New England while their father is off to the Civil War.
Based on the novel, Little women, by Louisa May Alcott.
Produced by Denise Di Novi , co-producer, Robin Swicord ; music by Thomas Newman ; screenplay by Robin Swicord ; directed by Gillian Armstrong.
Winona Ryder, Gabriel Byrne, Trini Alvarado, Samantha Mathis, Kirsten Dunst, Claire Danes, Christian Bale, Eric Stoltz, Mary Wickes and Susan Sarandon.
VHS format.
Closed captioned for the hearing impaired.
Keywords: Family -- New England -- Drama; Sisters -- New England -- Drama; Feature films